No evidence of association between HRV and training volume in a pool of professional athletes before, during, and after the first COVID-19 lockdown - Javaloyes, A.; Marinazzo, D.; Sanabria, D.; Moya-Ramón, M.; Lillo-Bevia, J. R.; Mateo-March, M. (Science & Sports, 2024)
PURPOSE: The COVID-19 crisis also affected elite sport severely, as elite athletes either stopped or drastically reduced their training regimen due to the lack of competitions and the mandatory lockdown. The aim of this study was to test whether heart rate variability was a reliable index of training load, which was dramatically altered due to the mandatory lockdown that occurred as a consequence of the COVID-19. METHODS: Training (volume and intensity) and heart rate variability of sixteen professional male (n = 8; body mass index = 22.2 ± 2.0) and female cyclists (n = 8; body mass index = 20.3 ± 1.1) before (4 weeks), during (7 weeks), and after (4 weeks) the mandatory lockdown in Spain were monitored. RESULTS: Individual analyses showed that the mandatory lockdown caused reliable reductions in training volume in 13 subjects (-96 to -7 % reductions in minutes), that were followed by an increase after the lockdown in all subjects (5 to 270%). In contrast, changes in training load were not homogenous across individuals. Moreover, such changes were not matched by comparable variations in heart rate variability. A mixed model of the heart rate variability as a function of training volume and intensity revealed no significant modulation by these two variables, and subject specific effects on the slope. CONCLUSIONS: In this study, we did not find evidence of association between heart rate variability and training load and/or intensity as many previous reports have suggested, even if training conditions changed dramatically overnight.